Meloidogyne incognita Penyebab Umbi Berbintil pada Kentang di Beberapa Sentra Produksi Kentang di Jawa - Aprilyani Aprilyani; Supramana Supramana; Gede Suastika (Jurnal Fitopatologi Indonesia, 2015)
Root knot nematodes is an important pathogen on potatoes in tropical and sub-tropical areas. Root knot nematodes contribute a significant impact in reducing the quality and quantity of potato tuber. Meloidogyne incognita is one of the species causing the root knot. This research was conducted to identify M. incognita on potatoes in Java Island based on morphological and DNA molecular characteristic. The infected potato tubers with pimple-like knot symptom were collected from Pangalengan (West Java), Banjarnegara (Central Java), and Kota Batu (East Java). Nematode was identified based on morphological character of perineal pattern, and based on molecular DNA character by polymerase chain reaction technique using a pair of specific primer (MI-F and MI-R), followed by DNA fragment sequencing and phylogenetic analysis. Based on morphological character of perineal pattern, M. incognita was detected in all 3 locations; while based on DNA molecular character, and M. incognita was detected in Pangalengan (West Java) and Kota Batu (East Java). M. incognita from Pangalengan had high homology, i.e.99.2% to 99.8% with those isolates from China, India, and Malaysia.